PROBLEM MASYARAKAT ACEH DI KOTA MEDAN TERHADAP PELAKSANAAN SYARIAT ISLAM - Yusda Novianti (Jurnal Sintaksis, 2019)
Approach in culture anthropology, relevant with a purpose to watchfulness culture ecology theory. Influence existence possibility from environment towards culture is thinking only see environment that has influence that limit culture that is that certain activity impossible happens in certain climates (like agriculture culture at pole region), so that only seen as something that doesn't has direct influence towards culture. Will approach dynamics (dynamic approach) will see syariat Islam from the aspect of will look at the implementation. In course of eksploration how does program execution or this activity is carried out, do conflicts that, different idea, importance difference that colour decision-making processes. Approach this more give top priority factors digging process born it decision, how is consensus created. This "watchfulness is carried out at field district petisah, and field district area,